Trends in Opioid Prescribing and Dispensing by Veterinarians in Pennsylvania - Clarke, Dana L. (JAMA Netw Open, 2019)
IMPORTANCE: Veterinarians are a subset of opioid prescribers. OBJECTIVE: To assess the quantity and trends in prescribing and dispensing of several different opioids in the past 11 years in a large veterinary hospital in Philadelphia, Pennsylvania. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study inventoried all opioid tablets and/or patches dispensed or prescribed by veterinarians practicing in a multispecialty academic veterinary teaching hospital in Philadelphia for small animals and species, such as rabbits, birds, and reptiles, from January 1, 2007, through December 31, 2017. Prescribing data were obtained from all veterinarians who wrote a prescription for opioids by reviewing detailed pharmacy records of controlled substances for the study period. Data included all opioids dispensed, or prescribed to animals (patients) undergoing evaluation at the center or being followed up as outpatients by the veterinarians in the hospital. Statewide veterinarian prescribing data were used for comparison. Data were analyzed from December 24, 2017, through May 15, 2018. MAIN OUTCOMES AND MEASURES: The trend in administration and prescribing of 4 specific opioid analgesics (codeine sulfate, hydrocodone bitartrate, and tramadol hydrochloride tablets as well as fentanyl citrate patch) during the 11-year study period. The individual opioids were converted to morphine milligram equivalents (MME) for comparison. RESULTS: The study included 134 veterinarians (70.9% women) with 366 468 patient visits. During the study period, the hospital veterinarians prescribed 1 051 836 tablets of tramadol, 97 547 tablets of hydrocodone, 38 939 tablets of codeine, and 3153 fentanyl patches to dogs (73.0%), cats (22.5%), and exotic animals (4.5%). Overall, MME use increased 41.2%, whereas visits increased by 12.8%. The comparison data for Pennsylvania revealed a predominance of hydrocodone use (688 340 tablets prescribed), although data were not available for comparison with tramadol because it is a Schedule IV drug. CONCLUSIONS AND RELEVANCE: Results of this study suggest that the large, increasing volume of opioids prescribed at 1 veterinary teaching hospital highlights concerns parallel to those about excessive opioid prescribing in humans. The extent to which these data may represent similar volumes of prescriptions from the general veterinary practices and hospitals across the United States is suggested by the accompanying Pennsylvania state data. These findings highlight an opportunity to assess the risk of veterinarian opioid prescriptions to safeguard public health.